Impacts of complex electromagnetic radiation and low-frequency noise exposure conditions on the cognitive function of operators - Liang, Peng; Li, Zenglei; Li, Jiangjing; Wei, Jing; Li, Jing; Zhang, Shenghao; Xu, Shenglong; Liu, Zhaohui; Wang, Jin (Frontiers in Public Health, 2023)
Background: Both electromagnetic radiation (EMR) and low-frequency noise (LFN) are widespread and influential environmental factors, and operators are inevitably exposed to both EMR and LFN within a complex exposure environment. The potential adverse effects of such exposure on human health must be considered seriously. This study aimed to investigate the effects of EMR and LFN on cognitive function as well as their interaction effect, which remain unclear. Methods: Sixty young male college students were randomly grouped and experiments were conducted with a 2×2 factorial design in a shielded chamber. Mental workload (MWL) levels of the study subjects were measured and assessed using the NASA-task load index (TLX) subjective scale, an n-back task paradigm, and the functional near-infrared spectroscopy (fNIRS) imaging technique. Results: For the 3-back task, the NASA-TLX subjective scale revealed a statistically significant main effect of LFN intensity, which enhanced the subjects' MWL level (F =8.716, p <0.01). Behavioral performance revealed that EMR intensity (430.1357 MHz, 10.75 W/m2) and LFN intensity (0-200 Hz, 72.9 dB) had a synergistic interaction effect, and the correct response time was statistically significantly prolonged by the combined exposure (F =4.343, p <0.05). The fNIRS imaging technique revealed a synergistic interaction effect between operational EMR intensity and operational LFN intensity, with statistically significant effects on the activation levels in the left and right dorsolateral prefrontal cortex (DLPFC). The mean β values of DLPFC were significantly increased (L-DLPFC F=5.391, p<0.05, R-DLPFC F=4.222, p<0.05), and the relative concentrations of oxyhemoglobin in the DLPFC were also significantly increased (L-DLPFC F=4.925, p<0.05, R-DLPFC F=9.715, p<0.01). Conclusions: We found a statistically significant interaction effect between EMR (430.1357 MHz, 10.75 W/m2) and LFN (0-200 Hz, 72.9 dB) when simultaneously exposing subjects to both for 30 min. We conclude that exposure to this complex environment can cause a statistically significant increase in the MWL level of operators, and even alterations in their cognitive function.